The Disaster Preparedness and Mitigation in Indonesia During the Covid-19 Pandemic in Indonesia: A Narrative Overview - Aisyah, Hesty; Edison, Elisa Daniati; Tasnim, M (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2023)
This paper presents the results of literature reviews on disaster mitigation preparation during the Pandemic Covid-19 since 2019. Of the 780 articles selected 6 articles on this topic published in national and international journals between Mei 2019 and June 2021 were included in the review. These articles are written in different disaster contexts, including events related to weather (floods and storms), natural disasters (earthquakes and tsunamis), and other events (such as pandemics and terrorist attacks). The main themes that arise include lack of communication between stakeholders, media sensationalism, the importance of choosing the most effective marketing messages, lack of disaster management plans, image damage, and goal reputation, and changes in tourist behavior after a crisis and disaster. This review identifies ways to increase the speed and effectiveness of responses to disasters, the importance of marketing relationships with loyal customers, and the need to quickly improve the image of the goal. Suggestions for future research arising from this review include the urgent need to encourage tourism operators to be involved with crisis readiness and disaster management strategies and the importance of getting a better understanding of consumer responses to disaster events.